2023
DOI: 10.1021/acsanm.3c00576
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Selectivity Functionality of a ZnO Nanotetrapod-Based Volatile Organic Compound Sensor Using Au Nanoparticle Decoration

Abstract: Gas sensors with multiselectivity are drawing increasing attention and sensors with temperature-tuned dual selectivity have been developed. Because Au nanoparticles (NPs) can lower the activation barrier for sensing reactions, herein, Au NP decoration was used to expand the selectivity range of a ZnO nanotetrapod (NTP)based sensor. A temperature-tuned triselectivity sensor based on Au NP−ZnO NTPs was developed. The sensor exhibited enhanced selectivity for formaldehyde when the operation temperature was <200 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…Accordingly, to improve the sensor response and selectivity towards the required gases, different approaches have been investigated. Surface modification with sensitizers like Au, CuO, NiO, PdO and Pt [4][5][6][7] is one of the most commonly employed method. Incorporation of sensitizers has been found to improve the response characteristics, which is attributed to the increase in the number of gas-specific selective sites for interaction with the target gas [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, to improve the sensor response and selectivity towards the required gases, different approaches have been investigated. Surface modification with sensitizers like Au, CuO, NiO, PdO and Pt [4][5][6][7] is one of the most commonly employed method. Incorporation of sensitizers has been found to improve the response characteristics, which is attributed to the increase in the number of gas-specific selective sites for interaction with the target gas [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Wencui Kang et al fabricated a nano-colorimetric sensor array consisting of nano-chemo responsive materials, which are used to quantify the volatile alcohols (VAs) in the kombucha tea extract fermentation process [3]. Au nanoparticles decorated ZnO nanotetrapod sensors with temperature-dependent selectivity were created by Fang Xu [4]. The sensor showed higher selectivity for formaldehyde at temperatures below 200 • C, ethanol at temperatures between 200 and 340 • C, and acetone at temperatures over 400 • C. Decorating TiO 2 gas sensors with Au nanoparticles improves sensor sensitivity by 40% according to Mostafa Shooshtari et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…One well-known way to improve the sensing properties of SnO 2 is to add certain dopants, such as transition metals and noble metals [ 16 , 30 , 31 , 32 , 33 , 34 , 35 ]. Previous studies have demonstrated that an extrinsic doping/co-doping strategy has a significant influence on the sensing performance (e.g., sensitivity, selectivity, and working temperature) [ 16 , 17 , 30 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%